A study on micronucleus frequency in lymphocytes by flow cytometry to assess genetic damage in Polycystic ovarian syndrome (PCOS) - R. Showri; T. Rajini (Al Ameen Medical College, 2022)
Background: Micronucleus is a small additional nucleus formed due to chromosomal loss or fragmentation and frequently used as a biomarker of genomic damage. Genetic damage and cancer susceptibility are notable concerns in PCOS. The aim of this study was to estimate the frequency of micronuclei in lymphocytes and to determine if it can be used as a biomarker of genomic instability in PCOS through flow cytometric analysis. Methods: An observational case control study was conducted among 38 subjects diagnosed with PCOS by Rotterdam's criteria and 38 controls from September 2018 to March 2020 in VIMS & RC. Peripheral venous blood samples were collected from all the subjects for flow cytometric assessment of micronuclei frequency in lymphocytes. Differences between the PCOS group and the control group were examined for statistical significance using two-sample independent t-test. The frequency of micronuclei in lymphocytes was expressed as mean ± SD. A P value of ≤0.05 denoted statistically signifi¬cant difference. Results: The mean ± SD of micronuclei frequencies in lymphocytes was observed to be 1.71 ± 0.88 and 0.43 ± 0.24 (p-value <0.0001) in PCOS and control group, respectively. Conclusion: This study is the first to use flow cytometric analysis in subjects with PCOS to detect micronuclei. The findings indicate that women with PCOS have an increased genomic instability as assessed by micronuclei frequency and thus it can be used a biomarker for genetic damage.